Peran Hukum Internasional Dalam Etnis Rohingya - Adri Sadewa Sirait; Ayu Ruth Kristiani Waruwu; Winda Windari Tarigan; Gita Maria Rehulina Sembiring; Opi Pibi Surbakti; Ira Silistiawati; Indra Utama Tanjung (Pusat Riset dan Inovasi Nasional, 2024)
The failure to prosecute the perpetrators of the Rohingya ethnic genocide crime is the beginning of the blunting of international law. The Rohingya ethnic group must get their Human Rights (HAM) back, as we know that Human Rights are basic rights that are inherent from birth by the grace of God and everyone must protect and respect them. Myanmar has a long history of human rights violations, according to Amnesty International. Suppression of freedom of expression and violations of human rights against underrepresented ethnic groups continue. The research used in this study uses normative juridical research methods with a case and legal history approach. In fact, institutional dogmatism is the result of the failure to protect human rights against ethnic groups. Rohingya, this study concludes that international law is blunt and only applies if there is a large benefit to the UN Security Council, the people of a country like Rohingya only suffer from injustice.